Riset Cerdas di Era Digital: Pemanfaatan AI, SLR dan ZOTERO dalam Penulisan Ilmiah untuk Mahasiswa - Roy Mubarak; Mubarak, Roy; Asruddin; Wawan Sismadi; Imam Riadi; Rusydi Umar (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The rapid digital transformation requires students to possess efficient and structured research literacy. This Community Empowerment Program (Prodamat) aims to enhance the research capacity of students at Politeknik Mitra Karya Mandiri through a